Trade, Envy and Growth: International Status Seeking in a Two-Country World - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
This paper analyzes international status seeking in a two-country model of endogenous growth: utility of agents in developing countries is aected by con- sumption gaps with the average consumer in advanced economies. By distorting terms of trade, status seeking: (i) may compensate for structural gaps in physical productivity, inducing convergence; (ii) may revert the link between trade and growth; and (iii) induces divergence when interacting with technological catching- up. In particular, envy in conjunction with catching-up predicts switchovers of growth leadership: when the advanced economy is both status- and technology- leader in the short run, convergence in interest rates - e.g. due to R&D spillovers - implies that the initially lagging economy becomes growth-leader in the long run, due to permanent price distortions induced by envy.
Keywords: D91; E21; F11; 330; Consumption externalities; international trade; two-country models; Zwei-Länder-Modell; Nachfrageinterdependenz; Wachstumstheorie